2005
DOI: 10.2747/0272-3638.26.4.328
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Married-Couple Dual-Earner Households on Metropolitan Commuting: Evidence from the Atlanta Metropolitan Area

Abstract: The idea of creating a balance between jobs and housing within different commuter catchment areas of a metropolis has been a prominent approach for reducing traffic congestion, air pollution, and journey-to-work times. Married-couple, dual-earner households, in which both spouses are employed, have been identified as an obstacle to the job-housing balance concept because of their constrained ability to choose a residential location near both workplaces. However, this has not yet been conclusively tested. Drawi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

8
55
3
3

Year Published

2006
2006
2021
2021

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 46 publications
(70 citation statements)
references
References 38 publications
8
55
3
3
Order By: Relevance
“…However, the total effect appears to be not significant. This finding supports Sultana (2005) who reported that there were either no significant differences in the average commuting duration between married-couple dualearner households and single-earner households, or if there were, the average commutes of single-earner households are longer. The direct and total effects of education attainment on the jobs-housing relationship are significant and positive, implying that workers with higher educational attainment are more likely to work and live in the same district.…”
Section: Modeling Resultssupporting
confidence: 93%
“…However, the total effect appears to be not significant. This finding supports Sultana (2005) who reported that there were either no significant differences in the average commuting duration between married-couple dualearner households and single-earner households, or if there were, the average commutes of single-earner households are longer. The direct and total effects of education attainment on the jobs-housing relationship are significant and positive, implying that workers with higher educational attainment are more likely to work and live in the same district.…”
Section: Modeling Resultssupporting
confidence: 93%
“…The growth of dual-earner families is viewed as a major obstacle undermining the implementation of jobs-housing balance policies, as it would be difficult to find a residence near the workplace of both the husband and the wife (Cervero, 1989). However, Madden (1981), along with Singell and Lillydahl (1986) and Sultana (2005), challenge this view. Their primary arguments are: 1) the residential location decisions of dual-earner households are mainly based on the job location of the male, who is deemed to be the major breadwinner; 2) due to the constraints of household responsibility, females in dual-earner households are more likely to take up jobs near the residence.…”
Section: Socio-demographic Characteristics and Urban Commutementioning
confidence: 95%
“…In the United States, female participation in the labour force and hence the number of dual-earner families have increased dramatically since the 1970s (Sultana, 2005). The growth of dual-earner families is viewed as a major obstacle undermining the implementation of jobs-housing balance policies, as it would be difficult to find a residence near the workplace of both the husband and the wife (Cervero, 1989).…”
Section: Socio-demographic Characteristics and Urban Commutementioning
confidence: 99%
“…Similarly, using data from the Seattle area, Clark et al (2003) reported that both singleand dual-earner households reduce commuting distances if they move from one residence to another, but pre-and post-move commutes are slightly higher for dual-earner households. On the other hand, drawing on the 2000 5% PUMS dataset for metropolitan Atlanta, Sultana's (2005) analysis shows that dual-earner households are more likely to reduce their commuting time compared to single-earner households, despite the fact that they may have more problems in balancing home and work locations. Her Wndings also conWrm that husbands in dual-earner households have shorter commutes than husbands in single-earner households, and hence the presence of wives in labor markets do not signiWcantly lengthen husbands' commuting time in dual-earner households.…”
mentioning
confidence: 97%